Two Kinds of Power: Insight Into The Legacy Of Patrick Wilson - Smiraglia, Richard P (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Among Patrick Wilson’s most influential books was Two Kinds of Power, which has influenced scholars in information science, and particularly in knowledge organization. Tools of domain analysis are used to analyze the corpus of literature that cites Two kinds of power. Aboutness and relevance are demonstrated keys to this specialization. Parmi les livres les plus influents de Patrick Wilson, on retrouve Two kinds of power, qui a influencé les disciples des sciences de l’information, particulièrement dans l’organisation des connaissances. Des outils de l’analyse de domaine sont utilisés pour analyser le corpus de littérature qui cite Two kinds of power. L’à-propos et la pertinence sont des clés manifestes de cette spécialisation.